Experimental Investigation and Numerical Simulation of the Microinjection Molding Process Through an Expanding Flow Configuration - Siginer, D (John Wiley and Sons Ltd, 2021)
The dependence of the induced morphological layer variations on the processing conditions and parameters during injection molding of polymers is analyzed through a robust numerical framework of the complete microinjection molding cycle. Predicted temperature, heat transfer and viscous dissipation, spherulite diameters, and shear rates provide sufficient clarifications to develop a deeper understanding of the complex evolution of the induced thicknesses of layers. The evolution of the structure of polyoxymethylene (POM) under strong strain rates and high thermal gradients is investigated while flowing along an expanding flow configuration composed of three steps of increasing thickness. High and low mold temperatures and injection velocity levels are tested according to the design of the experiment method (DOE). Morphological development in each zone was examined to provide the induced crystalline layer thickness in the longitudinal as well as the transverse directions using polarized light microscopy (PLM). The thickness of the layers strongly depends on the local thickness of the stepped-part and on the abrupt dimensional changes. The variation of bulk tensile properties obtained by dynamic mechanical analysis (DMA) is related to the thermomechanical history experienced by the melt. © 2021 John Wiley & Sons Ltd